2013
DOI: 10.3233/jad-121792
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with D3 Removes Amyloid Deposits, Reduces Inflammation, and Improves Cognition in Aged AβPP/PS1 Double Transgenic Mice

Abstract: One of the characteristic pathological hallmarks of Alzheimer’s disease (AD) is neuritic plaques. The sequence of events leading to deposition of amyloid-β (Aβ) peptides in plaques is not clear. Here we investigate the effects of D3, an Aβ oligomer directed D-enantiomeric peptide that was obtained from a mirror image phage display selection against monomeric or small oligomeric forms of Aβ42, on Aβ deposition in aged AβPP/PS1 double transgenic AD-model mice. Using Alzet minipumps, we infused the brains of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 59 publications
1
28
0
Order By: Relevance
“…We next sought to investigate whether known inhibitors of human pathological amyloid formation would effectively inhibit CsgA fibrillation on the basis of this proposed structural similarity. We tested a group of synthetic D-enantiomeric peptides (referred to here as D-peptides) designed against Aβ (55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65). Two of the D-peptides tested, ANK6 and DB3DB3 (60), were found to inhibit CsgA fibrillation in dose-dependent manners.…”
Section: Csga Shares Fibrillation Inhibitors With Aβmentioning
confidence: 99%
See 1 more Smart Citation
“…We next sought to investigate whether known inhibitors of human pathological amyloid formation would effectively inhibit CsgA fibrillation on the basis of this proposed structural similarity. We tested a group of synthetic D-enantiomeric peptides (referred to here as D-peptides) designed against Aβ (55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65). Two of the D-peptides tested, ANK6 and DB3DB3 (60), were found to inhibit CsgA fibrillation in dose-dependent manners.…”
Section: Csga Shares Fibrillation Inhibitors With Aβmentioning
confidence: 99%
“…The structural similarity between fibrillar spine segments derived from CsgA and those derived from human pathological amyloids prompted us to investigate whether fibrillation inhibitors designed against human amyloids could also inhibit curli formation. Accordingly, we found that two D-enantiomeric peptides, originally designed to interfere with the formation of oligomers of Alzheimer's disease-associated Aβ (55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65), inhibited the fibrillation of CsgA spines as well as of full-length CsgA and reduced biofilm formation in curli-expressing Salmonella typhimurium in dosedependent manners. These results provide structural insights into a biofilm-related amyloid and pave the way for the rational development of anti-microbial drugs targeting amyloid-structured biofilms.…”
Section: Introductionmentioning
confidence: 99%
“…One strategy to improve the peptide stability is the use of d -enantiomeric amino acids, which are considered to be rather protease resistant and often less immunogenic than the respective l -peptides [2022]. In addition, d -peptides were described to be absorbed systematically after oral administration [23], also shown for the Aβ oligomer precipitating d -enantiomeric peptide D3 in AD mouse models [27,49]. The PHF6 binding, d -enantiomeric peptides developed in this study were demonstrated to cross the membranes of N2a cells.…”
Section: Discussionmentioning
confidence: 99%
“…A retro-inverso peptide binding to a-synuclein antagonizes a-synuclein fibrillation in vitro and rescues behavioral deficits in a a-synuclein-transgenic Drosophila model [50]. D-peptide D3 improves brain memory functions upon intracerebral infusion into AD mouse models [25,51,52] and reduces the amyloid load within 30 days [25]. The compound PPI-1019 (methyl-LVFFL) completed clinical Phase I and II trials and was found to be well tolerated in humans and to cross the blood-brain barrier [53].…”
Section: Inhibitory Mechanisms With Therapeutic Perspectivesmentioning
confidence: 98%